2010
DOI: 10.1021/la104284v
|View full text |Cite
|
Sign up to set email alerts
|

Sonochemical Synthesis of Magnetic Janus Nanoparticles

Abstract: The sonochemical synthesis of nanosized surface-dissymmetrical (Janus) particles is described. The Janus particles were composed of silica and polystyrene, with the polystyrene portion loaded with nanosized magnetite particles. It is shown that the Janus particles can be used to form kinetically stable oil-in-water emulsions that can be spontaneously broken on application of an external magnetic field. The one-pot synthetic process used to prepare the Janus particles has several advantages over other conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(65 citation statements)
references
References 28 publications
0
62
2
1
Order By: Relevance
“…As shown in the EDX spectra obtained from isolated area of composite, there is no signal from the Fe or Si element in the neat region of the composite but relatively strong peaks from Si and Fe elements from the darker counterpart (inset of Figure 4). This is different from the results from Hatton and co-workers 35 regarding sonochemical synthesis, possibly because of different phase-separation behaviors. In this study, it was found that phase separation could be controlled by the addition of NH 4 OH to trigger the hydrolysis and polycondensation of TEOS with MPS molecules leading to the formation of a silica chain.…”
Section: Janus Fe 3 O 4 @Silica/polystyrene Composites Via Phase Sepacontrasting
confidence: 99%
“…As shown in the EDX spectra obtained from isolated area of composite, there is no signal from the Fe or Si element in the neat region of the composite but relatively strong peaks from Si and Fe elements from the darker counterpart (inset of Figure 4). This is different from the results from Hatton and co-workers 35 regarding sonochemical synthesis, possibly because of different phase-separation behaviors. In this study, it was found that phase separation could be controlled by the addition of NH 4 OH to trigger the hydrolysis and polycondensation of TEOS with MPS molecules leading to the formation of a silica chain.…”
Section: Janus Fe 3 O 4 @Silica/polystyrene Composites Via Phase Sepacontrasting
confidence: 99%
“…The most complex latex products made by ultrasound-induced-emulsion polymerization are nano-sized "Janus" particles, i.e., particles that are one-half hydrophilic and the other half hydrophobic [22]. Teo et al developed a sonochemical method whereby a silica particle and a polymer particle were conjoined.…”
Section: Polymer Latexmentioning
confidence: 99%
“…20,21 A number of reviews have been focused on these fabrication methods, their characteristic selfassembly and applications. 8,20,[28][29][30][31][32][33][34][35][36][37] Particularly, magnetic Janus particles have received remarkable attentions due to several advantages over other types of interaction; [28][29][30][31][32][33][34][35][36][37][38][39] the magnetic interaction is generally not influenced by surface chemistry of particles and characteristics of solvent such as pH, ionic concentration and its dielectric constant as in electric interaction. For example, not only orientation and motion of a single particle can be controlled but also field-induced suprastructures can be assembled in a reversible way.…”
Section: Introductionmentioning
confidence: 99%